Construction of Social Sustainability in Milk Production Systems in Central Mexico - Ruiz-Torres, M. E.; Lorga da Silva, A.; Arriaga-Jordán, C. M.; Martínez-Castañeda, F. E. (El Colegio de Postgraduados en Ciencias Agrícolas, Carretera México-Texcoco, 2021)
Objective: To build mathematical models to evaluate the social sustainability of small-scale milk production systems. Design/Methodology/Approach: Thirty small-scale cowsheds were analyzed. Two models were built using multivariate regression, estimated with ordinary least squares and considering the factors that producers perceive as important for social sustainability. Results: The first model (ER) included tangible variables and the second intangible variables (SR). Both models explained more than 80% of the variables associated with social sustainability. Study Limitations/Implications: The results represent an effort to link the statistical analysis with qualitative data that is difficult to quantify. Conclusions: The ER and SR models represent a proposal for counting immaterial indicators so they can be incorporated into the sustainability analysis. Both models could be a methodological proposal to connect statistical data with purely qualitative data such as perception.
Keywords: Livestock production; mathematical models; ethnography; social structures